Validated and culturally specific screening tools and early response programs for the detection and prevention of eating disorders among First Nations peoples in Australia: a scoping review - Mark John Castro; Zyana Gall; Alana Gall; Hilary Smith; Kanita Kunaratnam (Journal of Eating Disorders)
Abstract Background Eating disorders (EDs) are complex mental health conditions that can have severe health consequences, exacerbating the overall disease burden and causing significant economic impacts on healthcare systems. Globally, cultural and societal factors influence the presentation and management of these disorders, necessitating culturally specific approaches to screening and prevention. Among First Nations peoples in Australia, the intersection of historical, cultural, and social factors offers both context and strength in addressing EDs, while also presenting distinct challenges in identification and prevention. Objective This scoping review seeks to map and evaluate existing research on culturally specific and validated screening tools and early response programs tailored for the prevention and detection of EDs among the First Nations population in Australia. The goal is to acquire relevant information and identify gaps that need to be addressed in the literature to develop standardised screening tools and early response programs that are validated, effective, and culturally sensitive. Design A literature search was conducted through seven online academic databases (PubMed, MEDLINE, PsycINFO, Scopus, Web of Science, CINAHL, and Informit) and included publications from 2009 to 2024. The search strategy focused on ED prevention strategies among First Nations peoples in Australia, with emphasis on screening tools and early response programs. Results The scoping review found no culturally specific and validated screening tools and early response programs exist that have been specifically developed for First Nations peoples in Australia. After removing the cultural specificity criterion, seven studies were found that utilised six different screening tools and one early response program. Participant demographics across these studies were predominantly Caucasians or non-Indigenous, with First Nations individuals being underrepresented in sample sizes. Conclusion The findings reveal significant gaps in literature on culturally specific screening tools and early response programs for eating disorders among First Nations peoples in Australia. Existing studies often underrepresent these populations and rely on tools designed for non-Indigenous groups, questioning the generalisability of the effectiveness to First Nations peoples in Australia. This review emphasises the need for future research to adopt culturally competent methodologies led by First Nations peoples. Developing culturally specific tools and programs is crucial for improving health outcomes and achieving equitable mental health within Australian healthcare systems, ensuring that resources are justly distributed.